Different temporal integration of rod signals in luminance and chromatic pathways - Barrionuevo, Pablo Alejandro (2021)
To understand the integration of rod input (R) in luminance (L+M+S) and chromatic [L/(L+M)] pathways in the temporal dimension, we measured reaction times (RTs) to rod-isolating and/or pathway specific signals.A four-primary photostimulator based on the overlapped images of two spectrally-modified CRTs, which allowed independent stimulation of R, L, M and S photoreceptors, was used to generate rod (R), luminance (L+M+S) and chromatic [L/(L+M)] stimuli or the combination of rod and postreceptoral stimuli [L+M+S+R and R+L/(L+M)]. Light levels were from 0.5 cd/m2 to 6 cd/m2. The stimulus was a "C" target presented until participant's response or up to 4 s, measuring 4° of mean diameter. The target differed from the background only by its selected stimulation in a range of 3 or 4 positive and negative contrasts. Participants had to discriminate the position of the aperture of the C-Landolt ring while they fixate at a cross in the center of the "C", and respond as soon as they could. The reaction time (RT) was computed from the stimuli onset to the participant's response for each trial. RTs for L+M+S+R were higher than that for R or L+M+S stimuli. On the other hand, RTs for R+L/(L+M) were lower than that for R and L/(L+M) stimuli. Integration of rods signals differs in both pathways. For the luminance pathway, rod input reduced the processing speed, suggesting a suppressive rod-cone interaction. Surprisingly, the responses of the chromatic pathway were faster when rods were involved, suggesting a major role of rods in mesopic color perception.